The Systemic Approach to the Formation of Security of Insurance Business in Ukraine - Kopylyuk Oksana I.; Husar Ulyana Ye.; Muzychka Oleksandra М. (Bìznes Inform, 2018)
The article is aimed at improving the conceptual framework and developing a systemic approach to the formation of insurance business security in Ukraine. The authors’ approach to interpretation of the concept of security of insurance business, definition of its structure and elements is proposed. The methodological basis of formation of insurance business security system is substantiated with attention to the unity of interrelated elements; its key features are identified. It has been proved that efficiency of the insurance business security system is determined by its ability to withstand the factors of external and internal threats with the greatest efficiency, thus avoiding losses, preventing Insurance claims, minimize insurance indemnity and maximize the business profitability. Prospects for further researches in this direction are analysis and estimation of safety of the insurance market, improvement of both the indicator and another approaches to determination of the security level of insurance business on the basis of maximal congruence of insurance interests.